Engineering tolerance to CLCuD in transgenic Gossypium hirsutum cv. HS6 expressing Cotton leaf curl Multan virus-C4 intron hairpin - Mirza S. Baig (Nature Portfolio, 2021)
Abstract Cotton leaf curl disease (CLCuD), caused by begomoviruses in combination with betasatellite molecule, has adversely affected cotton industry of Indian subcontinent. To devise a CLCuD-control strategy, RNAi-mediated approach was followed in this study. Gossypium hirsutum cv. HS6 plants were transformed with intron-hairpin RNAi (ihpRNAi-C4) construct carrying silencing suppressor C4 gene of Cotton leaf curl Multan virus (CLCuMuV). Efficacy of the construct in imparting CLCuD resistance was evaluated in transgenic (T0, T1) cotton lines. Accumulation of CLCuMuV/betasatellite and attenuation of CLCuD symptoms in the transgenic lines were monitored at different times interval after virus inoculation. Northern hybridization revealed the expression of C4-gene derived siRNA. Expression of the ihpRNAi transcript was recorded higher in transgenic lines expressing siRNA which supposedly targeted the C4 gene. A significant delay in detection of virus as well as betasatellite was observed in the transgenic lines. At 30 days post inoculation (dpi), none of the lines tested positive. At 45 dpi, however, it could be detected in few lines having much lower titre as compared to non-transformed control plants. Notably, till 60 dpi, no significant progression of the virus/betasatellite DNA was observed and the plants did not exhibit any characteristic CLCuD symptoms. A tolerance phenomenon leading to escape of CLCuD symptoms in the transformed cotton was described.